Cure for increasing health care costs: The Bernhoven case as driver of new standards of appropriate care. Issue 3 (March 2019) - van Leersum, Nicoline; Bennemeer, Peter; Otten, Marcel; Visser, Sander; Klink, Ab; Kremer, Jan A.M.
Highlights: Investing in quality of care and a culture focused around 'appropriate care' results in lower burden of claims and lower costs. Unnecessary, unfounded care is prevented by investing in (more time for) clinical decision-making and shared decision with the patient. Contract and reimbursement innovation were developed in a hospital-insurer alliance and required to create the willingness for change. Reorganizing the hospital department organization into 4 multidisciplinary business units nourishes collaboration and patient-centered care. The burdens of claims was reduced by 16% in 3 year. Abstract: Containing costs is a major challenge in health care. Cost and quality are often seen as trade-offs, but high quality and low costs can go hand-in-hand as waste exists in unnecessary and unfounded care. In the Netherlands, two healthcare insurers and a hospital collaborate to improve quality of care and decrease healthcare costs. Their aim is to reduce unnecessary care by shifting the business model and culture from a focus on volume to a focus on quality. Key drivers to support this are taking time for integrated diagnosis ('first time right'), the right care at the right place and shared decision making between doctor and patient. Conditions to realize this are 1) contract innovation between the hospital and insurers to move away from fee-for-service reimbursement, 2) a culture change within the organization with emphasis on collaboration and empowerment of medical leadership and physicians to change daily practice, and 3) a reorganization of the hospital organization structure from a large number of medical departments to four business units related to the fundamental underlying patient need (acute care, solution shop, intervention unit and chronic care). Results from this whole-system-approach experiment show it is possible to provide better care (as experienced by patients) with lower volumes (16% lower DRG claims after 3 years) and provides valuable lessons for further healthcare reform.